Determination of micronutrients and colour variability among new plantain and banana hybrids flour - Adeniji, T.A.; Sanni, Lateef O.; Barimalaa, I.S.; Hart, A.D. (2006)
Quantitative colour variability and micronutrient content of new plantain and banana hybrids flour was investigated. The mean flour colour of the cultivars ranges from 12.16 for BITA 3 to 18.52 for FHIA 23, which is an indication of varying degree of yellowness. Both FHIA 23 and PITA 17 had colour value higher than the general sample means. Agbagba contained the highest level of iron (36.5 µg g ), which is higher than 1the overall sample means, followed by FHIA 17 (16.135 µg g ). The rest of the cultivars, including FHIA 171contained iron levels lower than the sample means. Similarly, Agbagba had the highest level (12.5 µg g ) of 1zinc, followed by FHIA 17 (12.49 µg g ). The value of zinc obtained in Agbagba, FHIA 17 and BITA 3 were 1higher than the general sample means. The total carotenoid contents of the cultivars are similar, with PITA 17 (4.795 µg g ), FHIA 17 (4.15 µg g ) and PITA 14 (3.815 µg g ) having values higher than the overall sample 111means. The estimated retinol equivalent of the flours ranges from 0.43 in FHIA 23 to 0.799 in PITA 17. The new Musa hybrids may be acceptable for increased production based on disease resistant, high yield and micronutrient content.